ANALYSIS OF JUDGMENT No. 40/PDT.G/2023/PN.BNA ON DEFAULT OF DAYAH BUILDING PROJECT ACCORDING TO THEORY OF IJARAH 'ALA AL-'AMAL - Sulthanul Akram Zulqahharsyah; Abd Razak (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2024)
The default case in the Dayah Safinatussalamah construction project in Aceh Singkil is an example of the complexity of implementing construction contracts based on ijârah 'ala al-'mâl contracts in Islamic law. CV Afdi Pratama as the contractor sued the Aceh Dyah Education Office for changes and additional costs that were not in accordance with the contract. This study aims to analyse the judge's consideration in rejecting the lawsuit over the construction contract dispute in Decision Number 40/Pdt.G/Pn.Bna and also the review of this decision according to the ijârah 'ala al-'amâl contract. The research method used is a normative juridical approach with a case study method. The main data is in the form of judge's decision documents, supported by literature review related to fiqh muamalah and contract regulations. Analysis was carried out qualitatively with content analysis to analyse trial facts, lawsuit materials, and legal considerations. The results showed that judges tended to use a formalistic approach by prioritising written evidence, ignoring technical realities and oral directions in project implementation. This decision does not reflect substantive justice, especially in recognising the plaintiff's right to additional costs due to work changes. In the perspective of ijârah 'la al-'amâl, this decision does not fully comply with the principles of justice (al-'is) and mutual consent (at-taradhin), which are the core of the contract in Islamic law so that the contract becomes fasid.